Identification of proteolytically resistant domains of human erythrocyte spectrin. - Speicher, D W (1980)
Digestion of purified human erthrocyte spectrin with proteolytic enzymes at 0 degrees C results in the production of intermediate-size peptides that resist further cleavage at 0 degrees C. By two-dimensional peptide analysis of these intermediate peptides it has been determined that five unique peptides are produced by tryptic cleavage of the alpha subunit of spectrin (band 1); these have apparent molecular weights of 80,000, 46,000, 46,000, 41,000, and 30,000 and account for 97% of the alpha subunit. Similarly, four unique peptides having apparent molecular weights of 74,000, 65,000, 33,000, and 38,000 account for 90% of the beta subunit (band 2). By examining larger peptide fragments, the linear alignment of the unique peptides along each of the spectrin subunits has been established. These results indicate that spectrin is composed of two nonidentical subunits, each containing multiple proteolytically resistant domains. These domains, which may be largely alpha-helical, seem to be connected by small protease-sensitive segments. The proteolytic resistance of these domains is not influenced by the multimeric state of the spectrin molecule.